The cost of rescuing the Peruvian business community - Mauro Machuca , Raúl (2014)
In 2008, the world faced one of the biggest economic and financial crises not seen since the 1930s. In response, the industrialized countries did not hesitate to implement a series of multibillion-dollar economic packages aimed primarily at rescuing companies. They had to do the same to stimulate household consumption. As a result of these interventions, the States were left severely indebted, which limited the optimal operation of their public services. For this last reason, a wave of cooperative solutions between the public and private sectors was promoted to take advantage of the latter's fresh resources to finance the former's infrastructure and public services.